After servitude : elusive property and the ethics of kinship in Bolivia - Winchell, Mareike, 1982- (University of California Press, 2022)
"How are injurious pasts redeployed by the dispossessed? After Servitude chronicles how agrarian engineers, indigenous farmers, Creole mining bosses, and rural workers navigate racial hierarchies rooted in histories of forced agrarian labor. In the rural Bolivian province of Ayopaya, where the liberatory promises of property remain elusive, Quechua people address such hierarchies by demanding aid from Creole elites and, where that fails, through acts of labor militancy. Against institutional faith in property ownership as a means to detach land and people, present and past, the kin of former masters and servants alike insisted that ethical debts from earlier racial violence stretch across epochs and formal land sales. What emerges is a vision of justice grounded in popular demands that wealth remain beholden to the region's agrarian past. By tracing this broader relational orientation to the past, Mareike Winchell demonstrates existing alternatives to property both as an extractive paradigm and as a technique of historical redress"--